Орфоэпическая компетенция в структуре коммуникатив- ного взаимодействия - Саримсакова, Н.К; Хакимова, Г.Т (FAN va JAMIYAT, 2024)
The article provides a structural-frequency analysis of the concept of orthoepic competence. The authors discuss the theoretical and methodological approaches of the Russian and Uzbek languages. And also in the structure of linguistic competence in the context of mastering Russian as a foreign language, the following series of relatively independent components were identified: lexical,